4(3w-6)=6(2w-4)

Simple and best practice solution for 4(3w-6)=6(2w-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3w-6)=6(2w-4) equation:



4(3w-6)=6(2w-4)
We move all terms to the left:
4(3w-6)-(6(2w-4))=0
We multiply parentheses
12w-(6(2w-4))-24=0
We calculate terms in parentheses: -(6(2w-4)), so:
6(2w-4)
We multiply parentheses
12w-24
Back to the equation:
-(12w-24)
We get rid of parentheses
12w-12w+24-24=0
We add all the numbers together, and all the variables
=0
w=0/1
w=0

See similar equations:

| 3=−2|1/4s−5|+3 | | x/5x-1=4/21 | | 4x/11=x/8+21 | | (50)(1+x)^10=200 | | 3z+5/4=-1 | | 2(x+8)=5x+5-3x+11 | | 23+18u=21u+14 | | 7x+6-3x=9x-4x+6 | | 8x-25+9+34=112 | | 15x-18=23-14 | | 9x-(4x-12)=37 | | z²-30=13z | | 13/3=v/5 | | 7=4y+4+2y | | ⅔y+7=15 | | -(x/5-6)+1=-8 | | 10−5x=−30 | | 3x+6=2+14 | | 3x+6+7x-18=-90 | | 3x+6+7x-18=0 | | 9x+72=4x+72 | | s=112+96(0.5)-16(0.5)^2 | | 9+3/4x-2/3x=11 | | s(0.5)=112+96(0.5)-16(0.5)^2 | | 720=460+(x+10)+x | | x=0.55555 | | 10y-7-2y=33 | | 5.8q-4.1-5.2q=-0.4q-2.4 | | X-(4x-7)=28 | | X-(4x-7)=24 | | 6z=3z+2(7+5z) | | 1.8q-3.6-5.7=-4.9q-2.7 |

Equations solver categories